Retail and modern trade survey to analyse the market prospect of BRAC Chicken - Khan, Muhammad Abdullah Asif (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.